Assessing the significance of Palaeolithic engraved cortexes. A case study from the Mousterian site of Kiik-Koba, Crimea - Majkić, Ana; d’Errico, Francesco; Stepanchuk, Vadim (PLOS ONE, 2018)
Twenty-Seven Lower and Middle Paleolithic sites from Europe and the Middle East are reported in the literature to have yielded incised stones. At eleven of these sites incisions are present on flint cortexes. Even when it is possible to demonstrate that the engravings are ancient and human made, it is often difficult to distinguish incisions resulting from functional activities such as butchery or use as a cutting board, from those produced deliberately, and even more difficult to identify the scope of the latter. In this paper we present results of the analysis of an engraved cortical flint flake found at Kiik-Koba, a key Mousterian site from Crimea, and create an interpretative framework to guide the interpretation of incised cortexes. The frame of inference that we propose allows for a reasoned evaluation of the actions playing a role in the marking process and aims at narrowing down the interpretation of the evidence. The object comes from layer IV, the same layer in which a Neanderthal child burial was unearthed, which contains a para-Micoquian industry of Kiik-Koba type dated to between c.35 and 37 cal kyr BP. The microscopic analysis and 3D reconstruction of the grooves on the cortex of this small flint flake, demonstrate that the incisions represent a deliberate engraving made by a skilled craftsman, probably with two different points. The lines are nearly perfectly framed into the cortex, testifying of well controlled motions. This is especially the case considering the small size of the object, which makes this a difficult task. The production of the engraving required excellent neuromotor and volitional control, which implies focused attention. Evaluation of the Kiik-Koba evidence in the light of the proposed interpretative framework supports the view that the engraving was made with a representational intent.